KONSEP SADD Al-DZARÎ’AH DALAM PERSPEKTIF IBNU AL-QAYYIM AL-JAUZIYAH - Imam Fawaid (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2019)
This Islamic law will continue to go along with the dynamics and changing of the era. The more complex real problems in society require fiqh experts to always be sensitive to reality. In producing the law, the jurists use various tools to produce laws that are in harmony with the benefit of mankind. This research is seen from the problems to be examined, the data collected is qualitative because it is in the form of thought, namely the conception of sadd al-dzarî'ah which was built by Islamic legal experts (fuqahâ 'and ushûliyyîn) in general and views on sadd al-dzarî'ah which was designed by Ibn al-Qayyim al-Jauziyah in his book I'lâm al-Muwaqqi'în. The concept of al-Dzarî'ah according to Ibn al-Qayyim can be used as an argument to establish the law. While the legal provisions of al-Dzarî'ah follow its (purpose). If the Ghâyah is in the form of benefit, then al-Dzarî'ah is opened and permitted, whereas if the Ghâyah is in the form of mafsadat, then al-Dzarî'ah is closed and prevented. The latter is what is called Sadd al-Dzarî'ah. For Ibn al-Qayyim Sadd al-Dzarî'ah, it can be used as an argument in determining the law because many texts of the Koran and Sunnah practice the concept of Sadd al-Dzarî'ah. Implicitly, these texts have legalized Sadd al-Dzarî'ah. However, if the practice in the field of Sadd al-Dzarî'ah is contrary to maslahat or hâjat, then Sadd al-Dzarî'ah is defeated. Benefits and hâjat are prioritized more than Sadd al-Dzarî'ah.